2023
DOI: 10.3390/antiox12061163
|View full text |Cite
|
Sign up to set email alerts
|

Mitochondrial Fission as a Therapeutic Target for Metabolic Diseases: Insights into Antioxidant Strategies

Abstract: Mitochondrial fission is a crucial process in maintaining metabolic homeostasis in normal physiology and under conditions of stress. Its dysregulation has been associated with several metabolic diseases, including, but not limited to, obesity, type 2 diabetes (T2DM), and cardiovascular diseases. Reactive oxygen species (ROS) serve a vital role in the genesis of these conditions, and mitochondria are both the main sites of ROS production and the primary targets of ROS. In this review, we explore the physiologic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
15
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 24 publications
(15 citation statements)
references
References 223 publications
0
15
0
Order By: Relevance
“…Additionally, dynamic balance between fission and fusion are crucial to maintain function and structure of mitochondria. Previous studies have identified that DRP1 is the mitochondrial fission core component, which is gathered into circular structure to mediate mitochondrial fission by mitochondrial cleavage alongside mitochondrial tubules [ 36 ]. OPA1 maintains fused mitochondrial network, and drives inner membrane fusion at the mitochondrial inner membrane [ 37 ].…”
Section: Discussionmentioning
confidence: 99%
“…Additionally, dynamic balance between fission and fusion are crucial to maintain function and structure of mitochondria. Previous studies have identified that DRP1 is the mitochondrial fission core component, which is gathered into circular structure to mediate mitochondrial fission by mitochondrial cleavage alongside mitochondrial tubules [ 36 ]. OPA1 maintains fused mitochondrial network, and drives inner membrane fusion at the mitochondrial inner membrane [ 37 ].…”
Section: Discussionmentioning
confidence: 99%
“…These processes maintain metabolic homeostasis in normal physiology and during cellular stress. Under physiological conditions, mitochondria undergo consistent fission and fusion to ensure homeostasis and energy adaptation but these are disrupted during pathological conditions [ 7 ].…”
Section: Mitochondrial Dysfunction and Diseasementioning
confidence: 99%
“…The accumulation of dysfunctional mitochondria is associated with the overproduction of mROS, mitochondria-controlled apoptosis, and chronic innate immune activation involved in age related diseases [ 6 ]. Mitophagy, which is the process of removing damaged mitochondria is impaired during pathological conditions [ 7 ]. Deregulation of MQC processes and ultimately mitochondrial dysfunction has been implicated in sarcopenia [ 16 ], glaucoma [ 17 ], lung disease [ 18 ], infection, obesity, type 2 diabetes/diabetes kidney disease [ 19 ], hepatic ischemia-reperfusion injury [ 20 ], cardiovascular disease [ 21 ], neurological diseases [ 22 ] and age-related diseases [ 9 , 23 ].…”
Section: Mitochondrial Dysfunction and Diseasementioning
confidence: 99%
See 2 more Smart Citations